2023
DOI: 10.1039/d3nr00177f
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing FASnI3-based perovskite light-emitting diodes with crystallization control

Abstract: The toxicity of lead presents a critical challenge for the application of perovskite optoelectronics. Lead-free perovskite solar cells were achieved with formamidinium tin iodide (FASnI3) perovskites, exhibiting decent power-conversion efficiencies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This absence of 2D perovskite phases differs from some previous reports where a large ratio (over 20 mol%) of ammonium ligands 18,24 and a different solvent composition 25 were employed in the precursor solutions to induce distinctive 2D/3D hybrid structures; on the other hand, the result is consistent with the studies where a similar amount of PEAI was used for fabricating 3D FASnI 3 light-emitting diodes. 26,27 Furthermore, the pristine and treated perovskite films show exactly the same diffraction peak positions (inset of Figure 3c), suggesting that the PEA and FPEA cations do not enter the 3D crystal lattice of FASnI 3 , consistent with previous reports. 21 It is worth noting that the FPEA-FASnI 3 perovskite film exhibits more intense (00l) diffraction peaks (Figure 3c) and narrower azimuthal angle of the (111) diffraction than the PEA-FASnI 3 film (Figure S11), suggesting higher crystallinity and a stronger preferential orientation of the former.…”
supporting
confidence: 89%
“…This absence of 2D perovskite phases differs from some previous reports where a large ratio (over 20 mol%) of ammonium ligands 18,24 and a different solvent composition 25 were employed in the precursor solutions to induce distinctive 2D/3D hybrid structures; on the other hand, the result is consistent with the studies where a similar amount of PEAI was used for fabricating 3D FASnI 3 light-emitting diodes. 26,27 Furthermore, the pristine and treated perovskite films show exactly the same diffraction peak positions (inset of Figure 3c), suggesting that the PEA and FPEA cations do not enter the 3D crystal lattice of FASnI 3 , consistent with previous reports. 21 It is worth noting that the FPEA-FASnI 3 perovskite film exhibits more intense (00l) diffraction peaks (Figure 3c) and narrower azimuthal angle of the (111) diffraction than the PEA-FASnI 3 film (Figure S11), suggesting higher crystallinity and a stronger preferential orientation of the former.…”
supporting
confidence: 89%
“…3D MASnI 3 , FASnI 3 , and CsSnI 3 films have been heavily investigated since their direct bandgaps, between 1.3 to 1.4 eV, could lead to intense PL emissions with minimal Stokes shifts. [283][284][285] On the other hand, some of these Sn-based perovskites have been synthesized as NCs, where the stronger quantum confinement tends to widen bandgaps and create more discrete energy levels. As a result, Sn-based perovskite NCs have PL peaks with narrower full width at half maxima (FWHM), which is advantageous for achieving higher color saturation and important for ultrahigh-definition displays.…”
Section: Sn and Ge-based Perovskite Ledsmentioning
confidence: 99%
“…[283,315] It has been shown that by controlling the crystallization process through the inclusion of additives such as phenethylamine iodide (PEAI) or SnF 2 , the operational lifetimes (time for the initial peak radiance of the LED to decrease by 50% under continuous operation) of FASnI 3 and CsSnBr 3 LEDs in an inert environment could exceed 10 and 30 hours (Figure 20b), respectively. [285,316] Recently, LEDs fabricated with 2D Sn-based perovskites have also gained more attention owing to their higher intrinsic stability in the air. Particularly, a pure-red EL with rather small FWHMs (less than 0.1 eV) have been demonstrated in (PEA) 2 SnI 4 as well as (TEA) 2 SnI 4 LEDs, and this EL was stable in a wide voltage range [299,317,57] (Figure 20b).…”
Section: Sn and Ge-based Perovskite Ledsmentioning
confidence: 99%
“…Over the past decade, optoelectronic devices based on metal-halide perovskites (MHPs) have achieved considerable development owing to the outstanding optoelectronic properties of MHPs. These successes also encourage the development of low-dimensional MHPs, aiming for further regulation of properties as well as new applications. , However, the widespread use of lead-based perovskites in MHP-based devices poses a significant challenge due to the toxicity of Pb, which hinders their further applications.…”
Section: Introductionmentioning
confidence: 99%